Multicenter Patch Testing With Methylisothiazolinone and Methylchloroisothiazolinone/Methylisothiazolinone Within the International Contact Dermatitis Research Group. Issue 3 (May 2017) - Isaksson, Marléne; Ale, Iris; Andersen, Klaus E.; Elsner, Peter; Goh, Chee-Leok; Goossens, An; Jerajani, Hemangi; Matsunaga, Kayoko; McFadden, John; Bruze, Magnus
Abstract : Background: The preservatives methylchloroisothiazolinone/methylisothiazolinone (MCI/MI) and MI are well-known contact sensitizers. Recently, an increase in the contact allergy frequency for MI 0.2% aqueous (aq) has been seen in many European countries paralleled with an increase in MCI/MI allergy. Many of the MI-allergic patients do not react to MCI/MI 0.01% or 0.02% because the concentration of MI in these preparations is too low (25 and 50 ppm, respectively) to elicit a positive patch test reaction. Objectives: The aims of this study were to investigate the prevalence of contact allergy to MI in the participating clinics representing various countries all over the world, to assess how many additional individuals with contact allergy are found by testing MI 0.2% aq in parallel with MCI/MI 0.02%, and to assess the clinical relevance of MI and MCI/MI allergies. Patients and Methods: In 9 dermatology clinics representing 9 countries, 3865 consecutive patients with dermatitis were patch tested with MI 0.2% aq and in parallel with MCI/MI 0.02% aq, provisionally included into the baseline series. An assessment of clinical relevance in those allergic to MI was also made. Results: Contact allergy to MI was found in 284 patients (7.3%). The frequency of contact allergy varied from 0.8% to 10.9% in different centers. Simultaneous reactivity to 200 ppm of MCI/MI was found in 67.3% of the MI-positive patients. Contact allergy to MI alone without any simultaneous contact allergy to 200 ppm of MCI/MI was diagnosed in 93 patients (32.7%; 2.4% of all tested patients). The contact allergy to MI and/or MCI/MI could explain or contribute to dermatitis in more than 60% of the MI-allergic patients. Conclusions: Methylisothiazolinone of 2000 ppm needs to be patch tested on its own to not miss contact allergy.